Assessing Effect of Marketing Practice on the Business Performance of Micro and small enterprise (MSE) in shashamenne town, Ethiopia. - Addisu Bekele Demie; Elia Muhammed; Nurhuseen Endris; Habtimer Mekonnen (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
AbstractThe main aim of this study is assessment of the effect of marketing practice on the business performance of micro and small MSE in shashemanne town, Ethiopia. In order to make the study being manageable it is necessary to define the delimitation of the study. Thus, the study were delimited conceptually, methodologically, time and geographically. Descriptive research design was applied. Both qualitative and quantitative types of data were used. Primary and secondary source of data was also applied. The target population for this study includes MSEs, workers, manager and owners of robe town micro and small scale enterprise office. The researchers was employed, both probability and non-probability sampling design, Proportionate Stratified sampling and Purposive sampling technique was used. The sample size of the study includes 10 government official from the sector leading organization and 319 from the Mse employees. Descriptive and inferential analysis was used. The model summary indicate the R2= 51.9 percent means that the total variation in the dependent variable (business performance is explained or caused by 51.9 percent of the change in all independent variables: MS, MC, AM, MMS and INF in connection with business performance of SME. The major finding of the study indicate that Marketing skill or hesitant to analyze existing business opportunities, managerial capacity are very critical for the them, poor infrastructure, problem of proximity to buyers and the following recommendation was forwarded based on the finding, MSEs are seen as an essential springboard for growth, job creation and social progress, solving shortage of local supply needs, provide training facilities and promote experience sharing programs, increase the capacity, knowledge and skill of the operators, experience sharing from successful enterprises